Associations of subjective cognitive and memory decline with depression, anxiety, and two-year change in objectively-assessed global cognition and memory. Issue 5 (3rd September 2022) - Sabatini, Serena; Woods, Robert T.; Ukoumunne, Obioha C.; Ballard, Clive; Collins, Rachel; Clare, Linda
ABSTRACT: Research studies exploring the association of cognitive complaints with objectively assessed cognitive decline report inconsistent results. However, many of these have methodological limitations. We investigated whether 1) more severe subjective cognitive decline (SCD) and subjective memory decline (SMD) predict change in objectively assessed global cognition, remote memory, recent memory, learning; 2) the predictive value of more severe SMD over change in objectively assessed remote memory, recent memory, and learning is stronger for individuals that report an SMD that started within the past five years than for those that report an SMD that started five or more years previously and/or stronger for those that experienced SMD within the past two years than for those who had not; and 3) greater depression and anxiety are associated with more severe SCD and SMD. We used two-year longitudinal data from the CFAS-Wales study (N = 1, 531; mean (SD) age = 73.0 (6.0) years). We fitted linear regression models. More severe SCD and SMD did not predict change in objectively assessed global cognition, remote memory, and recent memory but predicted lower scores in learning. The prediction of SMD over change in learning was not stronger when individuals reported an SMD that started within the past five years compared to when they reported an SMD that started five or more years previously nor when individuals reported an SMD that started within the past two years than those who did not. Greater depression and anxiety were associated with more severe SCD and SMD. More severe SMD may be useful for predicting lower learning ability and for identifying individuals experiencing depression and anxiety.